PERAN FILANTROPI ISLAM INTERNASIONAL DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI INDONESIA STUDI KASUS JAM’IYYAH IHYA AT-TURATS KUWAIT: PERAN FILANTROPI ISLAM INTERNASIONAL DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI INDONESIA STUDI KASUS JAM’IYYAH IHYA AT-TURATS KUWAIT - Khairunnisa; Adi Sanusi; Amad Chumsoni; N. Oneng Nurul Bariyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of international Islamic philanthropy in the development of Islamic educational institutions in Indonesia through a case study of Jam’iyyah Ihya At-Turats Kuwait. The research employed a descriptive qualitative approach using library research and case study methods based on data from various national and international references related to Islamic philanthropy and education. The findings reveal that Jam’iyyah Ihya At-Turats Kuwait has made significant contributions to the development of Islamic education in Indonesia through the network of Yayasan Lajnah Khairiyah Musytarokah. These contributions include the construction of schools, Islamic boarding schools, ma’had, educational mosques, student dormitories, educational scholarships, operational assistance, learning facilities, and the development of human resources in Islamic education. This international philanthropy has contributed to increasing access to education, improving the quality of Islamic educational institutions, and strengthening Islamic identity through Qur’anic memorization programs, Arabic language learning, and Islamic character development. However, this study also identifies several challenges in managing international philanthropy, including issues of legality, financial transparency, dependency on foreign donors, and the sustainability of educational programs. This study confirms that international Islamic philanthropy functions not only as a form of social assistance but also as an instrument for sustainable Islamic educational development.